2016
DOI: 10.1186/s41118-016-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

Intentions on desired length of stay among immigrants in Italy

Abstract: The decision to emigrate from the country of origin may not be a permanent one: migrants can decide to return home or to emigrate to a third country. This phenomenon, established for some time in certain other European countries, has become an important one for Italy only recently. This paper contributes to the knowledge of migrants' intentions in two ways: on the one hand, it analyses the factors associated with indecision about future plans; on the other, it focuses on the desired length of stay and its rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 59 publications
1
23
0
1
Order By: Relevance
“…For instance, Hazen and Alberts () in their study about international students in the Unites States found that family decisions and career advancements lead students with a temporary status to become permanent immigrants, regardless of their initial intentions to return to their country of origin. Nevertheless, several studies have demonstrated that intentions can be assumed as an essential premise of actual behaviours, because they are a proximate determinant of future actions (e.g., Barbiano di Belgiojoso, ; De Jong, ; Van Dalen & Henkens, ; Williams, Jephcote, Janta, & Li, ).…”
Section: Theoretical Background and Previous Findingsmentioning
confidence: 99%
“…For instance, Hazen and Alberts () in their study about international students in the Unites States found that family decisions and career advancements lead students with a temporary status to become permanent immigrants, regardless of their initial intentions to return to their country of origin. Nevertheless, several studies have demonstrated that intentions can be assumed as an essential premise of actual behaviours, because they are a proximate determinant of future actions (e.g., Barbiano di Belgiojoso, ; De Jong, ; Van Dalen & Henkens, ; Williams, Jephcote, Janta, & Li, ).…”
Section: Theoretical Background and Previous Findingsmentioning
confidence: 99%
“…Finally, identificational integration refers to subjective sense of belonging and identification, particularly in forms of ethnic and/or national, regional or local identifications (Heckmann 2007 ). Sense of belonging to the host country is extremely important for the integration process of any immigrant group, since it strengthens the attachment to the host society and reinforces the intention of a permanent and durable residence abroad (Barbiano di Belgiojoso 2016 ). The personal identity of immigrants and its recognition in a host society is also relevant in the process of integration (Heckmann 2007 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…During the lifetime migrants may change their future plans: if the decision to leave their home country may appear at the beginning of the migratory process as permanent, over time migrants may express the intention to come back home or to emigrate to another country. In such a context, it is relevant to analyse migrants’ future intentions since they may represent a good predictor and may influence actual behaviour on the return (Barbiano di Belgiojoso, ). In this respect, we believe that the knowledge of migrants’ plans and desires concerning return can facilitate researchers to better understand the migration experience, specifically its triggers and effects.…”
Section: Introductionmentioning
confidence: 99%